Applying ecological engineering for sustainable and resilient rice production systems - Horgan, Finbarr G.; Ramal, Angelee Fame; Bernal, Carmencita C.; Villegas, James M.; Stuart, Alexander M.; Almazan, Maria L.P. (Elsevier, 2016)
Global changes will affect rice ecosystems at local levels. Although issues of climate change have received most attention, other global changes will have more immediate impacts on crop productivity and health. These changes include the phenomenal advances in modern industrial output, especially in China and India, in mechanization, in communications technology and advertizing, in transportation networks and connectivity, as well as demographic shifts toward urban centers. Driven by policies around food security, market impacts on crop production, and trade regulations, these changes will define crop production systems into the future, impacting rice biodiversity and ecosystem function and giving rise to new pest and disease scenarios. This paper presents a framework for a holistic approach to ‘rice ecosystem health’ aimed at securing food production while protecting farmer, consumer and ecosystem health. Recent advances in environmentally friendly agriculture, including ecological engineering, are central to the sustainability and resilience of rice ecosystems; but require support from policy to ensure their best effects. This paper introduces some recent advances in the methods of ecological engineering based on research conducted in the Philippines